Mecanismo neuroprotetor da guanosina no modelo de comportamento do tipo depressivo induzido por lipopolissacarídeo em camundongos - Santos, Rozielly Aparecida Lemes dos (2022)
Guanosine is a purinergic nucleoside, released more intensely in events of injury, has anticonvulsant, amnestic and anxiolytic characteristics through its ability to modulate the glutamatergic excitatory system. Stimulation of astrocytic glutamate uptake suggests a potential role for guanosine in the treatment of diseases associated with glutamatergic excitotoxicity. The increase in pro-inflammatory cytokines triggers the activation of the enzyme indoleamine 2, 3 dioxygenase (IDO-1), leading to glutamatergic excitotoxicity and exacerbated activation of the hypothalamic-pituitary- adrenal axis (HPA), both with important roles in the pathophysiology of depression. The aim of this study was to investigate the association between the antidepressant- like effect of guanosine and lipopolysaccharide (LPS)-induced inflammation in the hippocampus of Swiss mice. The animals were submitted to pre-treatments with saline (0.9% NaCl orally), guanosine (8 or 16mg/kg po) and fluoxetine (20 mg/kg po) for 7 days, treatment with LPS (0.5mg /kg) occurred one hour after the last treatment. Pretreatment with guanosine was able to prevent depressive-like behavior in tail suspension test (TST) and forced swimming test (FST). In the open field test, no locomotor changes were observed. Our findings suggest that guanosine may have neuroprotective and neuroinflammatory effects against LPS-induced depressive-like behavior due to prevention in IDO-1 and TNF-α levels.